2017
DOI: 10.1159/000454981
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Estrogen Receptor 1 Regulates Human Neutrophil Functions

Abstract: Background: The role of estrogens in immune functioning is relatively well known under both physiological and pathological conditions. Neutrophils are the most abundant circulating leukocytes in humans, and their abundance and function are regulated by estrogens, since they express estrogen receptors (ERs). Traditionally, estrogens were thought to act via classical nuclear ERs, namely ERα and ERβ. However, it was observed that some estrogens induced biological effects only minutes after their application. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…GPER activation has a variety of effects on innate immune function, including modulation of macrophage cytokine production and neutrophil function 3032 , as well as reversing stroke-induced immunosuppression 33 . To determine whether GPER activation would support innate immune defense against infectious disease, we evaluated the effects of GPER activation on the outcomes of S. aureus infection using a well characterized murine model of SSTI 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GPER activation has a variety of effects on innate immune function, including modulation of macrophage cytokine production and neutrophil function 3032 , as well as reversing stroke-induced immunosuppression 33 . To determine whether GPER activation would support innate immune defense against infectious disease, we evaluated the effects of GPER activation on the outcomes of S. aureus infection using a well characterized murine model of SSTI 9 .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the G protein-coupled estrogen receptor (GPER) has been recognized as mediating many of the rapid and even long-term effects of estrogen 28,29 . GPER activation has been shown to modulate macrophage cytokine production and neutrophil function 3032 , as well as to reverse stroke-induced peripheral immunosuppression in ovariectomized mice 33 . Interestingly, GPER activation by the highly selective GPER agonist G-1 34 has also been reported to block disruption of endothelial barrier integrity as shown by its ability to limit blood-brain barrier (BBB) disruption following global cerebral ischemia (GCI) 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, G-1 promoted the expression of IL1B, CXCL2, COX2, SOCS3, GCSF, and IL1RA genes and increased the production of CXCL8 protein. These effects occurred through the cAMP/PKA/CREB, p38 MAPK, and ERK signaling pathways (98). G-1 magnified the effect of eotaxin on eosinophil chemotaxis and inhibited spontaneous apoptosis of eosinophils by reducing caspase-3 activity, but it had the opposite effect on eosinophils previously stimulated with IL-5, a cytokine that promotes their survival in eosinophilic inflammation, inducing apoptosis by increasing caspase-3 activity.…”
Section: Relationship Between Gper and Immune Responsementioning
confidence: 97%
“…Previous reports have shown that polymorphonuclear cells express the classical ERα and ERβ estrogen receptors, which were believed to have mostly anti-inflammatory actions ( 45 , 46 ). Contrary to these reports regarding the effects of estrogen on neutrophils, G1 activation of GPER1 triggered a proinflammatory reaction with increased cytokine (IL1b, CXCL8) and COX2 expression, enhanced respiratory burst and increased life span ( 36 ). This finding supports a differential role of GPER1, compared to classical estrogen receptors, in regulating inflammation in these cells.…”
Section: Expression and Function Of Gper1 By Cells Of The Immune Systmentioning
confidence: 61%
“…In the few studies that included intracellular signaling, the major GPER1-related pathways involved extracellular signal-regulated kinase 1/2 (ERK1/2), phosphoinositide 3-kinase (PI3K), and NFκB ( 26 , 29 , 32 ). In human neutrophils, the major pathways also involved cAMP/protein kinase A/cAMP-response element-binding protein, p38 mitogen-activated protein kinase, and ERK ( 36 ).…”
Section: Mechanisms Related To Gper1 Actions and Interactions With Otmentioning
confidence: 99%